Enhancing Performance in Learning Calculus 1 Through Integration of Technology - Paulino P. Malang; Bernandino P. Malang (Future Science / FSH-PH Publications, 2026)
This study compared the effectiveness of implementing the GeoGebra, which is a dynamic mathematics software, in the teaching of the Polynomial Curve Sketching (PCS) module of Calculus 1. More specifically, it aimed at determining if there was any improvement in students' achievement in graphing polynomials after using GeoGebra as compared to traditional teaching and also at finding out the students' learning experiences after the intervention. This study was carried out as a classroom-based action research using a quasi-experimental pre test-post test comparison design with the two intact classes of first year Bachelor of Science in Mathematics students from Bulacan State University. Control group= 55 students, experimental group= 55 students. The intervention took place in a 5-hour teaching unit, within one week. Students' achievement was assessed by researcher-made pretest and posttest on Polynomial Curve Sketching and Focus Group Discussions (FGD) were carried out to gain qualitative information about students' experiences of using GeoGebra. The results showed that both groups made progress following instruction but that the experimental group made greater progress on the post test than the control group. The experimental group increased from a mean pretest score of 4.4520 (SD = 2.1068) to a mean posttest score of 10.0302 (SD = 1.9881), whereas the control group improved from a mean pretest score of 4.1241 (SD = 1.6123) to a mean posttest score of 7.4733 (SD = 3.0592).